Analysis of the Potential Impact of Transfer Stations on Waste Transportation Patterns in Bandung City: A GIS-Based Approach - Amalia Dengo, Vita; Chaerul, Mochammad (Green Publisher, 2024)
The increasing population has led to higher consumption and the generation of household waste, particularly in the Bandung Raya area. The Legok Nangka Final Processing and Disposal Site (TPPAS) is planned as a solution for regional waste management after the Sarimukti landfill has completed its operational period. The service area of the Legok Nangka TPPAS follows the service area of the Sarimukti landfill, which includes the City of Bandung, the City of Cimahi, Bandung Regency, and West Bandung Regency. Given the existing conditions of the Legok Nangka TPPAS location, which is relatively far from the city and regency centers that generate waste, an alternative Intermediate Transfer Station (SPA) is needed. This facility can reduce waste volume while increasing waste density by three times. This research focuses on analyzing alternative locations for the Intermediate Transfer Station (SPA) in the City of Bandung to enhance the efficiency of waste transportation to the Legok Nangka TPPAS using Geographic Information System (GIS) based on Network Analysis. The results of this study indicate that the implementation of the Intermediate Transfer Station (SPA) significantly improves waste transportation efficiency. With a capacity of 500 tons per day, the SPA reduces the volume of waste directly sent to the Legok Nangka TPPAS by 26%. The distance and travel time for trucks are reduced by 23.97% for pool 1 and 25.91% for pool 2, respectively. Efficiency is also evident in the reduction of fuel consumption and carbon emissions, with decreases of up to 25.91%. The average number of trips required is 83 trips per day, indicating a reduction in long-distance travel to the TPPAS. These findings underscore the importance of the SPA in sustainable waste management in the City of Bandung.